The Effect of Worried Doll Therapy on Pre-School Age Anxiety Levels With Hospitalization In Rumkital Dr. Ramelan Surabaya - Dedi Irawandi (Journal of Global Pharma Technology, 2020)
Background: Play therapy is an effort to change problematic behavior by placing children in play situations. Anxiety is a pathological condition characterized by feelings of fear accompanied by somatic signs, a sign of a hyperactive autonomic nervous system. The aim of this study was to analyze the effectiveness of